2018
DOI: 10.3892/mco.2018.1621
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of cell‑free tumor DNA sequencing from the cerebrospinal fluid to guide treatment in a patient with primary leptomeningeal melanoma: A case report

Abstract: Primary leptomeningeal melanoma (PLM) is a rare type of cancer that represents a major clinical and molecular diagnostic challenge. A definitive diagnosis requires consistent magnetic resonance imaging findings and cerebrospinal fluid (CSF) cytology. Due to the small number of malignant cells in the CSF, routine testing for mutations in the gene is difficult, which prevents the stratification of these patients to potentially beneficial therapies. We herein present the case of a 62-year old man with CSF cytolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Most current studies of CSF cfDNA are small and retrospective. A few case reports have demonstrated that CSF cfDNA has been used clinically to guide (Melms et al, 2018;Guo et al, 2019) and monitor response to therapy (Siravegna et al, 2017). Prospective trials, however, are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most current studies of CSF cfDNA are small and retrospective. A few case reports have demonstrated that CSF cfDNA has been used clinically to guide (Melms et al, 2018;Guo et al, 2019) and monitor response to therapy (Siravegna et al, 2017). Prospective trials, however, are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…They can also be used to answer specific directed questions. For example, this approach can be used when knowing the presence or absence of a single genetic change will provide a diagnosis (see the discussion above of PCNSL and brainstem tumors), direct targeted therapy, i.e., MEK inhibitors in BRAF V600E mutated CNS melanoma (Melms et al, 2018), or provide prognostic information, i.e., TERT promoter variants in malignant gliomas (Shankar et al, 2015). Multiple PCR assays can be combined into small panels with relatively fast turn-around time, but analytical sensitivity may be impacted (see discussion above on glioma classification).…”
Section: Analytical Strategies: Targeted Vs Broad Approachesmentioning
confidence: 99%
“…Analysis of CSF ctDNA has also been demonstrated to provide insights into mechanisms of acquired resistance that might be confined to the CNS and might better represent the genomic landscape of leptomeningeal disease 20 , 96 , 97 . A number of case reports describing patients with melanoma suggest that CSF ctDNA might provide a useful method of monitoring intracranial disease response or identifying CNS-restricted targetable alterations, although these findings have not been validated in larger cohorts thus far 89 , 98 , 99 .…”
Section: Csf Ctdnamentioning
confidence: 99%
“…CtDNA in CSF may provide an alternative tool for detection of CNS-only disease and has been shown to be more sensitive than plasma ctDNA in this context [59][60][61]. A number of case reports have suggested that CSF ctDNA may be useful for monitoring intracranial disease response or identifying targetable mutations, but there have not been any large studies performed in melanoma to validate these findings [62,63]. In addition, CSF ctDNA may be useful in the diagnosis of leptomeningeal disease where radiological diagnosis can be challenging and cytological material in the CSF may be limited or even where present may be insufficient to permit analysis for BRAF mutations [64].…”
Section: Central Nervous System Diseasementioning
confidence: 99%